2021
DOI: 10.1073/pnas.2017715118
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic competition between SARS-CoV-2 NSP1 and mRNA on the human ribosome inhibits translation initiation

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a beta-CoV that recently emerged as a human pathogen and is the causative agent of the COVID-19 pandemic. A molecular framework of how the virus manipulates host cellular machinery to facilitate infection remains unclear. Here, we focus on SARS-CoV-2 NSP1, which is proposed to be a virulence factor that inhibits protein synthesis by directly binding the human ribosome. We demonstrate biochemically that NSP1 inhibits translation of model human and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
154
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 78 publications
(94 reference statements)
6
154
1
Order By: Relevance
“…While a previous study has established the crucial role played by N in viral genome processing and nucleocapsid assembly (Carlson et al, 2020), to the best of our knowledge there have been no prior reports specifically highlighting its ability to elevate lentiviral spike pseudovirus infectivity. It bears mentioning that similar to existent reports (Min et al, 2020;Schubert et al, 2020;Thoms et al, 2020;Lapointe et al, 2021;Zhang et al, 2021), the Nsp1 protein presumably exerts a detrimental effect on the host cell's protein translation, as indicated by the almost imperceptible extent of infectivity observed in its case (Figure 2A).…”
Section: Discussionsupporting
confidence: 83%
“…While a previous study has established the crucial role played by N in viral genome processing and nucleocapsid assembly (Carlson et al, 2020), to the best of our knowledge there have been no prior reports specifically highlighting its ability to elevate lentiviral spike pseudovirus infectivity. It bears mentioning that similar to existent reports (Min et al, 2020;Schubert et al, 2020;Thoms et al, 2020;Lapointe et al, 2021;Zhang et al, 2021), the Nsp1 protein presumably exerts a detrimental effect on the host cell's protein translation, as indicated by the almost imperceptible extent of infectivity observed in its case (Figure 2A).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, ATF3 is anti-inflammatory, reducing IL6 and IL12B transcription as part of a negative feedback loop [45]. Restriction in ATF3 protein expression may contribute to un-controlled IL6 production in cells that overcome the translational block, either through competition with ever increasing amounts of IL6 mRNA [46] or through an increase in IL6 mRNA stability enacted by the balance of RNA binding proteins ZC3H12A (Regenase-1) and ARID5A [47]. The latter of which stabilizes IL6 and is negatively regulated by MAPK14 (p38 MAPK) to resolve inflammation [48].…”
Section: Discussionmentioning
confidence: 99%
“…mRNAs using CLAR are less dependent upon scanning mechanisms performed by EIF4F/EIF4A and initiate more efficiently [66]. Mechanisms of translation inhibition occurring prior to mRNA engagement, i.e., virally encoded Nsp1 [46] and host encoded 4E-BP1 [67] should be less effective on closed loop mRNAs. While there currently lacks direct evidence that CLAR ribosomes resist translation inhibition by viral Nsp1 or host 4E-BP1, the increased representation of unstable mRNAs in downregulated genes shown here, combined with a potential for reduced access to the mRNA entry tunnel in CLAR ribosomes suggests this might be the case and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, no cellular or CoV-2 leader sequence mRNA binding was detected using nsp1 K164A/H165, which fails to engage the 40S subunit. However, recent in vitro data also argue against nsp1 binding ribosomes that have already engaged mRNA in their entry channel, or eIF3j-bound ribosomes that have a ‘closed head’ conformation 25,26 . Thus, mRNA binding by nsp1 presumably occurs subsequent to nsp1-40S binding and/or with mRNA that is associated with the 40S subunit but has not yet engaged the entry channel.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies revealed that the C-terminal helices of nsp1 dock within the entry channel through interactions with the RPS2, RPS3 and RPS30A ribosomal proteins as well as 18S rRNA 2225 . These interactions are likely allosterically enhanced by the initiation factor eIF1, perhaps because eIF1 induces an ‘open head’ conformation of the 40S subunit mRNA entry channel that is favorable for nsp1 binding 26 . In addition to blocking translation, SARS CoV nsp1 also promotes cleavage of mRNA near the transcript 5’ end and CoV-2 nsp1 similarly reduces mRNA levels in cells 1921,27 .…”
Section: Introductionmentioning
confidence: 99%